The extraction of trichlorostannato-rhodium complexes by polyurethane foam - Hall, Iris (Department of Chemistry, 2016)
Polyurethane foam (polyether based) has been found to efficiently extract rhodium from hydrochloric acid solutions containing stannous chloride. The amount of rhodium extracted is significantly influenced by inter alia temperature, acid concentration, the Sn(II):Rh mol ratio and the presence of alkali metal cations. The extraction efficiency is promoted by increased acid concentration and high Sn(II):Rh ratios. The presence of K⁺ inhibits the extraction of rhodium, while the effect of Li⁺ and Na⁺ is small. A series of model urethane compounds (diurethane podands and linear polyurethanes) have been synthesized and characterized. These model compounds allowed the direct determination of the extracted trichlorostannato·rhodium complex anions by ¹¹⁹Sn nmr spectroscopy. Conditions favouring the formation of [Rh(SnCl₃)₅]⁴⁻ were found to result in the extraction of increased amounts of rhodium. The predominant species in the urethane phase was identified as the hydrido complex, [RhH(SnCl₃)₅]³⁻, which is formed by protonation of [Rh(SnCl₃)₅]⁴⁻. The protonation reaction has been shown to be reversible. The ¹¹⁹Sn nmr study showed the formation of a new rhodium-hydrido complex formulated to be [RhH(SnCl₃)₄Cl]³⁻. In the presence of low tin(II) concentrations {Sn(II):Rh = 4:1}, [Rh(SnCl₃)₃Cl₃]³⁻ is predominantly extracted by the foam phase. Analysis of the acid-decomposed polyurethane foam phase by atomic absorption spectroscopy and of the model urethane compound phase by ⁷Li nmr spectroscopy, confirmed the extraction of alkali metal cations from aqueous solutions containing alkali metal salts. Our studies indicate that the polyether chains of polyuretha foam playa major role in the extraction process, and that the flexibility of the chains influences the efficiency of polyurethane foam as an extractant. The creation of cationic sites within the foam matrix, which facilitate the extraction of the rhodium-tin complex anions, is postulated to occur by protonation of the donor oxygen atoms as well as by chelation of cations such as H₃O⁺, Li⁺, Na⁺ and K⁺ by the polyether chains. A working model for the extraction of the trichlorostannato-rhodium complexes by polyurethane foam is proposed.